Prospecção de micro-organismos lignolíticos da microbiota amazônica para a produção de biocombustível de segunda geração e compostagem - Fernandes , Simone Maciel (2013)
With population growth , increasing food production and consequently tons of agricultural wastes are generated consisting of : cellulose, hemicellulose and lignin , forming the biomass which can be used as an alternative to obtain products with high added value. Microorganisms are the primary decomposers of organic matter, among the enzymes secreted by fungi are the ligninases and lipases. The ligninases act in the decomposition of recalcitrant compounds and their main producers are basidiomycetos, using the liginina and cellulose as a source of carbon and energy. Lipases have as its main substrates oils and fats and have a comprehensive field of biotechnological applications. Due to the importance of using organic matter of vegetable origin and diversity of micro-organisms capable of producing several enzymes with biotechnological applications , this research aimed to select fungi capable of converting biomass into biofuel 2nd generation and composting. Thus, to obtain ligninases 10 fungal strains were used: five Basidiomycetos and five Penicillium spp , as substrates: bagasse (BCn), and passion fruit peel (CMJ and SMJ) , peel and seed cupuaçu (CCp and SCp), cassava peels (CMx ), annatto (CUr), guarana (CGu), coconut (CCc) and pie rosewood (TPR). The 10 strains and five Aspergillius spp. were used to obtain the lipases, using as substrates SMJ, SCp and olive oil (OL). The strains were grown at 26 and 28 ° C for 240h at 120rpm in submerged fermentation (FSM ) growth of all strains in substrates 11 reviews observable. The enzyme extract was obtained by vacuum filtration then centrifuged in 2 ml Eppendorf tubes for 10 minutes at 10,000 rpm again transferred to clean Eppendorf tubes and stored under refrigeration. Chemical analysis revealed that the manganese peroxidase (MnP) was more expressed in most substrates with the highest activities produced by Penicillium sp. 1 enzyme (Pen 1 ), except only the Cp and CMj , with the greatest amounts of lignin peroxidase (LiP ) obtained by basidiomyceto 1 (Bas 1) . For laccase (Lac) the basidiomycetos were the best producers, and only in CCc, CMx and CMj all Penicillium spp . produced this enzyme. For the highest lipase activity was detected in the substrate OL . by Aspergillus sp . 1 (Asp 1), followed by the SCP Aspergillus sp. 4 (Asp 4). Of the three tested substrates was observed that the SMJ was the best inducer, since there was production by 14 of the 15 strains used , with the sole exception of Aspergillus sp. 3 (Asp 3), basidiomycetes and the ones that were produced using at least two substrates . In the composting process both strains were used: Bas 1 and Pen 1 and cultured in the CMJ for 90 days. After this period originated compounds were weighed and observed degradation of approximately 80 % of the waste that had the presence of micro -organisms , the lowest weight in compounds containing the CMJ previously autoclaved , and the control group remained unchanged , are the weights of the compounds varied with the conditions of each experiment. The produced compounds planting was carried Curcubita sp. And 30 days observed their development, with the best growth observed in compounds containing the residue over autoclaved inocula Bas 1 and Pen 1. These results confirm the potential of these fungi produce ligninases and lipases using agricultural wastes as substrates for the production of second generation biofuels and composting.